New relationship between Energy and Estrada Index
Let G be a graph on n vertices, and let λ_1, …,λ_n be its eigenvalues. The energy E(G) of a graph G is defined as the sum of absolute values of the eigenvalues of G. The Estrada index of the graph G is defined as EE(G)=^n _i=1e^λ_i . We get some new bounds for EE(G). Some special inequalities are used to obtain the relationship between E(G) and EE(G)., number=4, journal=Discontinuity, Nonlinearity, and Complexity, author=Li, Yalan and Deng, Bo and Ye, Chengfu, year=2026, month=Aug., pages=617–623